Functional and emotional outcomes after transient ischemic attack: A 12-month prospective controlled cohort study. Issue 5 (July 2019) - Sackley, Catherine M; Mant, Jonathan; McManus, Richard J; Humphreys, Glyn; Sharp, Leslie; Mares, Kathryn; Savva, George M
Background: Symptoms of transient ischemic attack are believed to fully resolve within 24 h of onset. Emerging evidence suggests that there may be prolonged functional and psychological impact, although studies have not been able to robustly identify whether these are the effect of transient ischemic attack or changes usually associated with ageing. We describe trajectories of disability and risk of anxiety and depression among patients seen at transient ischemic attack clinics over 12 months, compared to healthy controls. Methods: Thirty transient ischemic attack clinics across England participated. A total of 1320 participants were included: 373 diagnosed with transient ischemic attack, 186 with minor stroke, 310 with "possible transient ischemic attack, " 213 with another condition mimicking a transient ischemic attack and 238 controls recruited from primary care providers. Participants completed questionnaires after diagnosis then after 3, 6 and 12 months. Outcomes were the Nottingham Extended Activities of Daily Living Scale and the Hospital Anxiety and Depression Scale. Mixed effects regression was used to estimate group differences and trajectories. Results: At baseline, confirmed transient ischemic attack patients scored 1.31 HADS-Anxiety points (s.e. = 0.28; p < 0.001), 0.51 HADS-Depression points (s.e. = 0.26; p = 0.056), and 2.6 NEADL points (s.e. = 1.1; p = 0.020) worse than controls. At 12 months, the deficits were 0.78 (s.e. = 0.30; p = 0.008), 0.97 (s.e. = 0.23; p < 0.001), and 0.96 (s.e. = 0.92; p = 0.294) respectively. Differences among patients diagnosed with minor stroke were like or worse than transient ischemic attack patients. Conclusions: Transient ischemic attack clinic patients may have functional and emotional impairments compared to the general population irrespective of final diagnosis. The presence of emotional symptoms or risk of developing anxiety or depression did not always fully recover and may increase.